2019
DOI: 10.1002/ange.201907572
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Stacking of Triplet Chromophores in the Crystal Form for Ultralong Organic Phosphorescence

Abstract: Provided here is evidence showing that the stacking between triplet chromophores playsacritical role in ultralong organic phosphorescence (UOP) generation within ac rystal. By varying the structure of afunctional unit, and different onoff UOP behavior was observed for each structure.R emarkably,24CPhCz, having the strongest intermolecular interaction between carbazole units exhibited the most impressive UOP with along lifetime of 1.06 sand aphosphorescence quantum yield of 2.5 %. 34CPhCz showed dual-emission U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…38,39 The shorter lifetime of orbital transition demonstrates that the recombination rate of triplet state to ground state is very fast, which can effectively reduce the loss of nonradiative decay, resulting in an increase in the intensity of red emission with the decrease in temperature (Figure S9), which suggests that at low temperatures triplet states become more stable by suppressing nonradiative relaxation from thermal and collisional processes. 40,41 Hence, it is evident that the peak at 400−435 nm corresponds to fluorescence emission and that at 625 nm corresponds to phosphorescence emission, emitting radiation from the singlet excited state and triplet excited state, respectively. Furthermore, we deduce that the blue fluorescence is from the CQD core, whereas the enhancement of red phosphorescence is attributed to the extensive framework, which was verified by controlled experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…38,39 The shorter lifetime of orbital transition demonstrates that the recombination rate of triplet state to ground state is very fast, which can effectively reduce the loss of nonradiative decay, resulting in an increase in the intensity of red emission with the decrease in temperature (Figure S9), which suggests that at low temperatures triplet states become more stable by suppressing nonradiative relaxation from thermal and collisional processes. 40,41 Hence, it is evident that the peak at 400−435 nm corresponds to fluorescence emission and that at 625 nm corresponds to phosphorescence emission, emitting radiation from the singlet excited state and triplet excited state, respectively. Furthermore, we deduce that the blue fluorescence is from the CQD core, whereas the enhancement of red phosphorescence is attributed to the extensive framework, which was verified by controlled experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, a new type of organic luminescent materials with ultralong organic phosphorescence (UOP) has drawn considerable attentions owing to their distinctive advantages of long-lived persistent luminescence and high exciton utilization [12][13][14][15]. A library of UOP luminogens has been developed with a series of feasible strategies including crystal engineering [16][17][18][19][20][21][22][23], H-aggregation [24][25][26][27][28], host-guest doping [29][30][31][32], and so on [33][34][35][36][37][38][39][40][41][42][43][44], which mainly show steady-state phosphorescence emission at room temperature. Very recently, a dynamic photoactivated UOP was fortuitously found in triazines and phenothiazine derivatives under ambient conditions [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, such thermal effects are obstacles to high luminescent efficiency and therefore restrict the practical suitability of phosphors for commercial applications involving LEDs at high temperature. Quite recently, it was demonstrated that the introduction of intermediate energy levels or defect states for energy transfer in pure inorganic phosphors can diminish the TQ effect to some extent [23][24][25][26][27] ; however, examples of materials with zero-TQ emission are still rather rare, particularly for the case of molecular systems (Supplementary Table 1) [28][29][30] . Therefore, obtaining TQresistant materials remains an open challenge.…”
mentioning
confidence: 99%